resolva os sistemas {×-3= -y 3× +2=y+3
Soluções para a tarefa
Respondido por
0
Resposta:
x = 1 e y = 2
Explicação passo a passo:
x - 3 = - y ---> x = - y + 3
3x + 2 = y + 3
3x + 2 = y + 3
3 . (- y + 3) + 2 = y + 3
- 3y + 9 + 2 = y + 3
9 + 2 - 3 = y + 3y
8 = 4y
8 / 4 = y
2 = y
3x + 2 = y + 3
3x + 2 = 2 + 3
3x = 2 + 3 - 2
3x = 3
x = 3 / 3
x = 1
Perguntas interessantes
Inglês,
8 meses atrás
História,
8 meses atrás
Matemática,
8 meses atrás
Artes,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
1 ano atrás